The Relationship Between Mental Health and Periodontal Disease: Insights from NHANES Data [version 1; peer review: awaiting peer review] - AlJoghaiman, Eman (F1000 research, 2024)
Introduction and aim Periodontal disease, initiated by dental biofilm and influenced by various local and systemic factors, includes stress as a potential contributor to its progression. Despite associations with severe forms like acute necrotizing ulcerative gingivitis, a comprehensive large-sample study linking stress to periodontal disease is lacking. This study aims to investigate the relationship between mental health and periodontal disease. Materials and Methods Leveraging data from the National Health and Nutrition Examination Survey (NHANES), relevant information was extracted. Mental health was the exposure variable, and periodontal disease, assessed through indices following Eke et al.'s definition, served as the outcome. Covariates impacting periodontal disease were considered, and demographic and disease status analyses employed the Rao-Scott chi-squared test. A logistic regression model assessed mental health's impact on periodontal disease. Results Logistic regression indicated higher odds of periodontal disease among individuals feeling bad about themselves for more than half of the day (OR 1.170, 95% CI 0.533-2.474), though statistical significance was not reached. Periodontitis prevalence significantly varied based on marital status, with 6.6% of married and 10.8% of unmarried subjects affected. Notably, a statistically significant difference in periodontitis prevalence existed between subjects with health insurance (8.3%) and those without (16.5%). Conclusion Within study limitations, it is concluded that no significant difference exists in periodontal status between individuals with compromised mental health and those without. The findings underscore potential associations between mental health, marital status, and access to health insurance with periodontal disease.